2021
DOI: 10.1134/s0031918x2111003x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Iron and Silicon on the Phase Composition and Microstructure of the Al–2% Cu–2% Mn (wt %) Cold Rolled Alloy

Abstract: Experimental and computational techniques have been used to study the influence of Fe and Si, as probable impurities, on the phase composition and microstructure of the Al-2% Cu-2% Mn cold-rolled alloy (wt %). These elements in the total amount up to 0.4% have been found to join together into eutectic Al 15 (Fe,Mn) 2 Si 5 phase inclusions, which have no negative effect on the cold-rolling processability. The hardness and electrical conductivity of the annealed cold-rolled sheets are almost the same as those of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…As a result, the plastic deformation covers a much larger volume, which leads to the formation of deep dimples (Figure 9). As follows from previous works on Al-Cu-Mn system alloys in the concentration range considered [18][19][20][21][22][23], annealing at 400 °C and higher temperatures makes it possible to obtain a close-to-equilibrium state. Therefore, appropriate calculations of the phase composition were carried out for the test alloys.…”
Section: Discussionmentioning
confidence: 73%
“…As a result, the plastic deformation covers a much larger volume, which leads to the formation of deep dimples (Figure 9). As follows from previous works on Al-Cu-Mn system alloys in the concentration range considered [18][19][20][21][22][23], annealing at 400 °C and higher temperatures makes it possible to obtain a close-to-equilibrium state. Therefore, appropriate calculations of the phase composition were carried out for the test alloys.…”
Section: Discussionmentioning
confidence: 73%
“…The alloy of this chemical composition has high strength and ductility, and its processability is higher than that of standard alloys due to the fact that there is no need for any additional heat treatment. The authors of this alloy composition have also studied the possibility of its alloying with Zr [5], Fe and Si [6,7], as well as with Mg and Zn [8].…”
Section: Introductionmentioning
confidence: 99%
“…One should however bear in mind the high cost of Sc generally limiting its use as an alloying additive [24,25]. Other works [26][27][28][29] dealt with the effect of Si and Fe on the phase composition of Al-Cu-Mn alloys after different types of deformation and heat treatment. It was found that small additions of those elements (up to 0.4%) favor the precipitation of the Al 15 (Fe,Mn) 2 Si 3 (Al 15 ) and Al 6 (Fe,Mn,Cu) (Al 6 ) phases which decelerate the development of recrystallization processes in the alloy structure during long-term exposure to elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%